Patterns of iron and siderophore distributions across the California Current System. (9th November 2018) - Boiteau, Rene M.; Till, Claire P.; Coale, Tyler H.; Fitzsimmons, Jessica N.; Bruland, Kenneth W.; Repeta, Daniel J.
Abstract: Coastal upwelling of nutrients and metals along eastern boundary currents fuels some of the most biologically productive marine ecosystems. Although iron is a main driver of productivity in many of these regions, iron cycling and acquisition by microbes remain poorly constrained, in part due to the unknown composition of organic ligands that keep bioavailable iron in solution. In this study, we investigated organic ligand composition in discrete water samples collected across the highly productive California Coastal upwelling system. Siderophores were observed in distinct nutrient regimes at concentrations ranging from 1 pM to 18 pM. Near the shallow continental shelf, ferrioxamine B was observed in recently upwelled, high chlorophyll surface waters while synechobactins were identified within nepheloid layers at 60–90 m depth. In offshore waters characterized by intermediate chlorophyll, iron, and nitrate concentrations, we found amphibactins and an unknown siderophore with a molecular formula of C33 H58 O8 N5 Fe. Highest concentrations were measured in the photic zone, however, amphibactins were also found in waters as deep as 1500 m. The distribution of siderophores provides evidence for microbial iron deficiency across a range of nutrient regimes and indicates siderophore production and acquisition is an important strategy for biological iron uptake in iron limited coastal systems. Polydisperse humic ligands were also detected throughout the water column and were particularly abundant near the benthic boundary. Our results highlight the fine‐scale spatial heterogeneity of metal ligand composition in an upwelling environment and elucidate distinct sources that include biological production and the degradation of organic matter in suboxic waters.